Deep brain stimulation outcomes and management of childhood‐onset dystonia and associated hyperkinetic movements disorders - Sinead Barkey; Laura Ainaga; Eva Maria Navarrete Muñoz; Verity McClelland; Keyoumars Ashkan; Richard Selway; Harutomo Hasegawa; Daniel E Lumsden; Jean‐Pierre Lin; Hortensia Gimeno (Developmental Medicine & Child Neurology, 2026)
Abstract Aim To examine longitudinal changes in self‐selected goals and dystonia severity over 1 year, 2 years, and 5 years after deep brain stimulation (DBS) in children and young people (CYP) with dystonia and other hyperkinetic movement disorders, using CYP and caregiver reports. Method The retrospective cohort study included follow‐up to 5 years after DBS, with the number of participants varying across time points. In the CYP group, 62 participants were included at the 1‐year follow‐up, 50 at 2 years, and 17 at 5 years. In the parental and caregiver sample, 146 participants were included at 1 year, 125 at 2 years, and 51 at 5 years. Changes across time were assessed using Wilcoxon signed‐rank tests, the Canadian Occupational Performance Measure (COPM), and Burke–Fahn–Marsden Dystonia Rating Scale ‐ motor severity (BFMDRS‐m). Analyses were stratified by key characteristics of participants, including sex, age at surgery, Manual Ability Classification System (MACS) level, Gross Motor Function Classification System (GMFCS) level, and aetiology. Results Median COPM performance increased from 2.8 to 6.1 (baseline to 5 years), while COPM satisfaction improved from 2.6 to 7.6; parent/caregiver reports showed similar trends. BFMDRS‐m scores decreased from 81.0 to 70.0, with the largest improvements in the first year. COPM changes were greater in monogenic dystonia and participants classified in MACS levels I to III. BFMDRS‐m improvements were more pronounced in monogenic dystonia, participants classified in GMFCS levels I to III, and those aged at least 12 years. Interpretation DBS showed sustained improvements in motor function and self‐selected goals, with consistent findings across CYP and caregiver reports. Functional gains were observed despite limited dystonia reduction, particularly in dystonic cerebral palsy.